A study of the durability of OPC vs. GGBS concrete on exposure to silage effluent - PAVIA, SARA (American Society of Civil engineers, 2008)
Ordinary portland cement (OPC) has been traditionally used in the construction of concrete silos in Ireland. However, the aggressive nature of the effluent produced by silage leads to severe degradation of the concrete. GGBS is a common addition to PC composites. It has been demonstrated that GGBS improves the general performance of PC concrete, decreasing chloride diffusion and chloride ion permeability, reducing creep and drying shrinkage, increasing sulfate resistance, enhancing ultimate compressive strength, and reducing heat of hydration and bleeding. It has also been suggested that GGBS may increase concrete durability in the aggressive environment of silos. In order to investigate this theory, a simulation study was carried out by immersing samples of mortars incorporating increasing amounts of GGBS in a silage effluent solution and a magnesium sulfate solution. Over the course of an experiment consisting of three, 28-day cycles of immersion in the silage effluent, the sample performance was evaluated by testing permeability, porosity, water absorption, capillary suction, compressive strength, and mass loss. According to the results obtained, the OPC samples suffered the highest rise in permeability and porosity, and the greatest loss in both mass and compressive strength. In addition, the durability of the mortars, when subjected to both salt crystallization and silage effluent cycles, increased with increasing amounts of GGBS. The significant rise in capillary suction, water absorption, and permeability over the course of the experiment indicates that the damage induced by the effluent is not as superficial as previously reported. Loss in mass and increase in permeability were found to be the most reliable indicators of corrosion, as they gave the most dramatic and uniform results.
PUBLISHED
Keywords: Civil, Structural & Environmental Engineering